DPM heads honours list: Kedah sultan's birthday: Muhyiddin will receive 'Datuk Seri Diraja' award - Shazwani, Ili (New Sunday Times, 2014)
DEPUTY Prime Minister Tan Sri Muhyiddin Yassin heads the list of 116 recipients who will be bestowed with titles and awards in conjunction with the 86th birthday of Sultan of Kedah Tuanku Abdul Halim Mu'adzam Shah today. Muhyiddin will be conferred the Darjah Seri Setia Sultan Abdul Halim Mu'adzam Shah Yang Amat Dihormati (SHMS), which carries the title "Datuk Seri Diraja".The investiture ceremony will be held at Istana Anak Bukit here today.